2015
DOI: 10.1523/jneurosci.4553-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Locus Ceruleus Neurons to Reward Value for Goal-Directed Actions

Abstract: The noradrenergic nucleus locus ceruleus (LC) is associated classically with arousal and attention. Recent data suggest that it might also play a role in motivation. To study how LC neuronal responses are related to motivational intensity, we recorded 121 single neurons from two monkeys while reward size (one, two, or four drops) and the manner of obtaining reward (passive vs active) were both manipulated. The monkeys received reward under three conditions: (1) releasing a bar when a visual target changed colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
114
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 38 publications
27
114
0
Order By: Relevance
“…Noradrenergic neurotransmission has traditionally been implicated in attention and arousal processes (Berridge and Waterhouse, 2003;Aston-Jones and Cohen, 2005), rather than motivation or reward. However, emerging work in rodents (Ventura et al, 2008) and primates (Bouret and Richmond, 2015) has indicated that noradrenergic neurotransmission may also modulate reward processes. Indeed, our recent work implicates prefrontal, amygdala, and habenula noradrenaline in social play behavior (Achterberg et al, 2015), which hints at the possibility that limbic noradrenaline is involved in certain emotional aspects of this behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Noradrenergic neurotransmission has traditionally been implicated in attention and arousal processes (Berridge and Waterhouse, 2003;Aston-Jones and Cohen, 2005), rather than motivation or reward. However, emerging work in rodents (Ventura et al, 2008) and primates (Bouret and Richmond, 2015) has indicated that noradrenergic neurotransmission may also modulate reward processes. Indeed, our recent work implicates prefrontal, amygdala, and habenula noradrenaline in social play behavior (Achterberg et al, 2015), which hints at the possibility that limbic noradrenaline is involved in certain emotional aspects of this behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that the activity of noradrenergic neurons reflects the effort needed to perform goal-directed actions (33,34): The higher the activity of the noradrenergic neurons in the locus coeruleus, the stronger the action. Amphetamine, which activates both dopamine and adrenergic receptors, greatly enhances movement activity.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly this LC response was shown to be better aligned to the movement compared to the stimuli presentation in and was not elicited either in the present of a response inhibition cue, or with the successful withholding of the movement (Kalwani et al, 2014). Interestingly, this LC response is elicited regardless of speed of response (Bouret & Richmond, 2009;Bouret & Richmond, 2015;, correctness Kalwani et al, 2014) or reward expectation -LC fires with action even when the animal did not anticipate reward- (Bouret & Richmond, 2015;Clayton et al, 2004). Furthermore the anticipation of effort needed to perform an action has been also shown to modulate LC firing suggesting that LC is also signalling the energy requirements of the movement (Varazzani et al, 2015).…”
Section: Norepinephrine and Voluntary Movementsmentioning
confidence: 91%
“…Interestingly, although a significant proportion of individual neurons displayed a firing modulation related to reward before the feedback in self-initiated trials, there was no modulation related to the reward size at the population level. Thus, the effects observed on individual neurons are not coherent enough to emerge at the level of the population (Bouret & Richmond, 2015).…”
Section: Norepinephrine and Voluntary Movementsmentioning
confidence: 96%
See 1 more Smart Citation